A Diagnostic Dilemma of White Matter Lesions and Cerebral Oedema without Identifiable Cause—A Neurological Conundrum - Namraj Goire; Michael Buckland; Ramesh Cuganesan; Sameer Saleem; Vivienne Lea; Roy G Beran (Brain Sciences, 2021)
Introduction: This paper describes a case of bi-frontal vasogenic oedema associated with bilateral frontal lobe and left parietal lobe white matter lesions where extensive investigations, including brain biopsy, failed to establish a diagnosis. Case Report: A 67-year-old female presented with three weeks’ history of memory loss, fatigue, insomnia, nausea, and occasional dysphasia. Physical examination was unremarkable, yet cerebral CT and MRI showed bilateral frontal lobe vasogenic oedema. Extensive investigations, including: biochemical; radiological; immunological; microbiological; haematological; histopathological; and cytological, failed to establish a confirmed diagnosis. A multidisciplinary team could not achieve a consensus for this atypical presentation. Brain biopsy was unusual, showing destructive inflammatory and subtly granulomatous disease, but an exhaustive list of auxiliary tests could not confirm a cause, and consensus favoured glial fibrillary acidic protein (GFAP) autoimmune encephalopathy. Discussion: A definitive diagnosis could not be established for this patient despite a gamut of investigations. Although some of the presenting features were consistent with GFAP astrocytopathy, initial staining of the patient’s CSF for neuronal antibodies was negative. Her symptoms and radiological changes of brain imaging improved without any corticosteroid therapy. Conclusions: Through this case report, the aim is to add to the repository of neurological sciences in the hope that future similar presentations could potentially lead to discovery of a new aetiology or contribute towards better understanding of an existing disease process.